1983
DOI: 10.1148/radiology.147.2.6300959
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter embolization of hepatocellular carcinoma: assessment of efficacy in cases of resection following embolization.

Abstract: In 8 cases of hepatocellular carcinoma, hepatectomy was performed after hepatic artery embolization with Gelfoam. Complete necrosis of the tumor was found in 4 of these cases. Compared with the tumors that showed incomplete necrosis, the tumor in the complete necrosis group were small, thickly encapsulated, and located at sites remote from collateral circulation. Angiography and computed tomography after embolization accurately demonstrated tumor necrosis or continued viability, as confirmed by examination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
0
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(59 citation statements)
references
References 0 publications
7
51
0
1
Order By: Relevance
“…[4][5][6][7][8] This study demonstrated that similar symptoms were observed in PCS, 3,4) and similar leukocytosis was also observed in PCS 10) ( Table 4). Recent studies have suggested that the etiology of PES is related to an inflammatory process/cascade and tissue ischemia and necrosis although there are some differences in blood flow preservation between PCS and PES.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…[4][5][6][7][8] This study demonstrated that similar symptoms were observed in PCS, 3,4) and similar leukocytosis was also observed in PCS 10) ( Table 4). Recent studies have suggested that the etiology of PES is related to an inflammatory process/cascade and tissue ischemia and necrosis although there are some differences in blood flow preservation between PCS and PES.…”
Section: Discussionsupporting
confidence: 81%
“…It has been speculated that these symptoms may be the result of an inflammatory response. [4][5][6][7][8] We define these symptoms as post-aneurysmal coiling syndrome (PCS). The purpose of this study is firstly to analyze the clinical risk factors of PCS, and secondly to prevent patients from experiencing PCS.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a wellrecognizable tumor capsule at the pretreatment CT scan was the most important independent predictive factor of MN after transcatheter treatment. According to our results, previous pathological studies performed on liver resection following transarterial chemoembolization [22,23] demonstrated that encapsulated HCCs are more responsive to the transcatheter treatment than nonencapsulated tumors. Interestingly, a significant correlation between the thickness of the capsule and the effectiveness of tumor necrosis after chemoembolization has also been documented [24,25] .…”
Section: Discussionsupporting
confidence: 72%
“…In the majority of cases, however, the tumors are not completely necrotized and the incidence of recurrence after TACE is still high (1)(2)(3). To prevent further complications and advanced stages of the disease with an unfavorable prognosis, it is critical that follow-up imaging studies focus on early recognition of intralesional viable tumors or localized recurrences.…”
mentioning
confidence: 99%